The use of information and communication technology to enhance professional learning communities of Setswana home language - Moduka, Sibongile Nomonde Patience (University of the Free State, 2019)
This study aimed to design a framework for using information and communication technology (ICT) to enhance professional learning communities (PLCs) of the subject Setswana home language. The 21st century requires that learners master new knowledge and skills if they are to proceed to the next level and meet the challenges presented by living in this century. Educational reforms related to the new knowledge and skills also affect teachers, as they also have to know what to teach and how to teach it. In order to keep abreast of these changes, teachers have to engage in intensive and continuous professional development. Communication and collaboration amongst subject teachers is crucial for both teacher development and learner attainment. Establishing PLCs is a collaborative approach to teaching, which involves teachers collaborating in order to empower each other, and sharing their best practices, with the aim of improving learner achievement. The functionality of face-to-face PLCs is, however, affected by a variety of factors, which, in turn, hinder the PLCs from achieving their goals. It is against this background that this research study emerged. This study investigated the challenges that led to the need to design a framework for using ICT to enhance PLCs of Setswana home language, and proposes solutions for the challenges. Furthermore, the conditions under which such a framework could be implemented, and the threats that could impede the implementation process, are reflected upon. The study also reveals evidence of the successful implementation of the framework. Critical emancipatory research was the theoretical framework that drove the study to achieve its aim and objectives, and to address the research question. This study was operationalised by applying the learning theory of connectivism, which takes into account trends in learning about the use of technology and networks. Participatory action research was the research approach used to generate data. The following members formed a team of co-researchers: district ICT coordinator, subject advisors, senior phase teachers, heads of departments, principals, a school governing body member and an administration clerk. Data generated through discussions during meetings and Whatsapp groups was analysed using Van Dijk’s critical discourse analysis, which uses three levels of data analysis: textual, social and discursive levels. The co-researchers found that ICT enhanced the assistance provided by PLCs to teachers, by helping them to communicate and collaborate and meet the curriculum needs of the 21st century. Teachers are able to reflect on their practices via ICT resources, they can participate in their own learning in a free environment, and they can elevate Setswana home language as a subject by developing their own, current multimedia texts and other materials, which they can share amongst themselves via ICTs. Lastly, the study recommends that ICT integration in curriculum practice should be supported fully by school leaders.
Dissertation (M.Ed. (Curriculum Studies))--University of the Free State, 2019
Keywords: Professional learning communities; Information and communication technologies; Setswana home language